Effect of high-temperature thermal hydrolysis on rheological properties and dewaterability of sludge. Issue 23 (15th October 2021) - Cao, Xiuqin; Pan, Yahong; Jiang, Kun; Zhu, Kaijin; Ren, Xiaoli
ABSTRACT: The disposal processes like dewatering and anaerobic digestion (AD) are commonly utilized to reduce the volume of sludge and recover energy. Thermal hydrolysis process is widely used as a pretreatment for sludge AD, which can change rheological properties and dehydration of sludge irreversibly. The experiment was designed to evaluate the effect of high-temperature thermal hydrolysis (120, 130, 145, 160 and 170°C) for 60 min on sludge rheological properties, as well as its dewaterability. Rheological tests were performed at (20 ± 0.1)°C with a HAAKE Viscotester 550 Rotary Viscometer. Both raw and thermal hydrolysis sludge has a considerable reduction on apparent viscosity and yield stress, but a somewhat increase in thixotropy. With the increase of temperature, the sludge flow behaviour index n increases linearly, while the consistency coefficient k follows the law of linear decline, showing that thermal hydrolysis can weaken the non-Newtonian fluid properties and then improve sludge fluidity. The dewaterability increases linearly with the temperature. Besides, the dewaterability of high-temperature thermal hydrolysis processes sludge was always significantly better than raw sludge as its mud cake has a much larger solid content. Notably, the increase in flow performance index n and the decrease of thixotropy kinetic coefficient K caused by thermal hydrolysis are all linear with the enhancement of dewaterability, which demonstrates that rheological indicators can be a new tool to evaluate the dewaterability of sludge. GRAPHICAL ABSTRACT: UF0001